Penerapan Teknik Kursi Kosong Untuk Meningkatkan Kepercayaan Diri Siswa MAN 1 Kota Ternate - Agustan Arifin, Andi (JURNAL KONSELING GUSJIGANG, 2023)
The purpose of this study was to determine the level of students’ self-confidence and to find out whether there was an effect of using the empty chair technique on increasing self-confidence in students of MAN 1 Ternate. This research used an experimental approach. The design used in this study was a simple experimental design (Posttest Only Control Group Design). The research subjects were 60 students of XI grade in MAN 1 Ternate. Collecting data used questionnaires and observations. Data analysis used descriptive and inferential analysis.The results showed that: (1) The level of self-confidence of students in the experimental group of class XI students of MAN 1 Ternate before being applied the empty chair technique was in the low category, after giving treatment, the level of student confidence increased, namely in the high category. Meanwhile, in the control group, the students' self-confidence at the pretest and posttest were in the low category. (2) There was an influence of students' self-confidence who were given the empty chair technique with students who were not given the empty chair technique. Key Word : Confidence, empty chair technique